2018
DOI: 10.1186/s13020-018-0175-z
|View full text |Cite
|
Sign up to set email alerts
|

Wenyang Huazhuo Tongluo formula inhibits fibrosis via suppressing Wnt/β-catenin signaling pathway in a Bleomycin-induced systemic sclerosis mouse model

Abstract: BackgroundSystemic sclerosis (SSc) is an autoimmune disease characterized by fibrosis of the skin and internal organs. So far, no Western medicine treatment can completely inhibit or reverse the progress of SSc, while at the same time, our previous series of studies have shown that the treatment of SSc by the Wenyang Huazhuo Tongluo formula (WYHZTL), a Chinese herbal decoction, shows a delightful prospect. The aim of this study is to further investigate the mechanism of anti-fibrosis of WYHZTL formula in SSc m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…Alkaloid berberine, as a traditional anti-inflammatory Chinese herbal medicine, can inhibit colon tumor formation through inhibition of Wnt/β-catenin signaling [36]. Wenyang Huazhuo Tongluo formula has anti-fibrosis effect in Bleomycin-induced SSc mouse model by inhibiting Wnt/β-catenin signaling pathway [37]. Thus, our study provides a valuable prototype for effective therapeutic agents in tumor treatment by inhibiting Wnt pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Alkaloid berberine, as a traditional anti-inflammatory Chinese herbal medicine, can inhibit colon tumor formation through inhibition of Wnt/β-catenin signaling [36]. Wenyang Huazhuo Tongluo formula has anti-fibrosis effect in Bleomycin-induced SSc mouse model by inhibiting Wnt/β-catenin signaling pathway [37]. Thus, our study provides a valuable prototype for effective therapeutic agents in tumor treatment by inhibiting Wnt pathway.…”
Section: Discussionmentioning
confidence: 99%
“…XAV-939 is one member of a large set of small-molecule inhibitors of the Wnt/β-catenin pathway [28, 39, 40]. Targeting of this pathway in clinical or experimental settings and the applicability of the inhibitors have several limitations, so ongoing drug design is focused on identifying additional specific inhibitors that have fewer side effects [39, 4143]. Members and proteins of the Wnt/β-catenin signalling or Notch signalling pathways may be new targets for drug development to prevent the progression of AV stenosis, since these signalling pathways are believed to be involved in osteogenesis in human AV disease [4, 9, 17, 33, 44].…”
Section: Discussionmentioning
confidence: 99%
“…Male C57/BL6N mice (purchased from Beijing Vital River Laboratory Animal Technology Co., Ltd.) aged 8 weeks and weighing 17-20 g were used to construct a bleomycin-induced SSc mouse model as previously described [ 8 ]. Briefy, 100 ul of bleomycin (200 ug/ml) was subcutaneous injected to the restricted area of the upper back each day, which lasted for 3 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies have shown that Wenyang Huazhuo Tongluo Formula regulated immune imbalance and exerts anti-fibrosis effects in the treatment of SSc. Wenyang Huazhuo Tongluo Formula exerts it anti-fibrosis effects by regulating the fibroblast cell cycle, inhibiting its proliferation, and reducing collagen synthesis by inhibiting the Wnt/β-catenin signaling pathway [ 8 – 10 ]. Wenyang Huazhuo Tongluo Formula can also inhibit the expression of type I and III collagen by inhibiting the TGF-β1/Smad signaling pathway in SSc fibroblasts.…”
Section: Introductionmentioning
confidence: 99%